PRIVATE MILITARY AND SECURITY COMPANIES: ETHICS, POLICIES AND CIVIL MILITARY RELATIONS/EDITED BY ANDREW ALEXANDRA, DEANE-PETER BAKER AND MARINA CAPARINI - Vreÿ, Francois (Scientia Militaria - South African Journal of Military Studies, 2011)
This publication contributes to a growing body of literature on a phenomenon, the privatization of the means of coercion, that manifests on the international strategic landscape. Whether a phenomenon one agrees with, or not, private military and security companies form an rising and real feature within the daily life of individuals, communities and states of the international system. International, regional and national security, as well as the security of the individual is increasingly entwined in services provided by private military and security contractors. The editors accordingly acknowledge that “… [the] astonishing growth of private and security companies (PMSCs) is clearly one of the most noteworthy developments in national and international security arrangements …”. The content of the publication covers three fields of enquiry: ethics, policies and law, and civil-military relations and stems from a research programme sponsored by South African, Australian and Swiss institutions. At the heart of the publication resides the inherent conflict and controversy between private contractors and the challenge they bring to traditional views regarding the regulation and operation of the control over force and its application. Inherently the publication attempts to contribute to the debate on how to regulate or control a new way of employing and controlling instruments of violence in the international system.